2022
DOI: 10.1039/d2sc01910h
|View full text |Cite
|
Sign up to set email alerts
|

A flexible functional module to regulate ultraviolet optical nonlinearity for achieving a balance between a second-harmonic generation response and birefringence

Abstract: The rigid planar π-conjugated groups are adopted for designing ultraviolet (UV) nonlinear optical (NLO) materials extensively. However, for these UV NLO crystals, the realization of strong second harmonic generation (SHG)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…And it is found that the introduction of uorine in the tetrahedron can enhance the birefringence or optimize the dispersion of refractive indices, TO 4−x F x (T = B, x = 1-4; T = P, x = 1-2; T = S, and x = 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] Planar p-conjugated anionic groups, such as BO 2 , BO 3 , B 3 O 6 , C 3 N 3 O 3 , CO 3 , NO 3 , etc., [35][36][37][38][39][40][41][42][43][44] Cite this: DOI: 10.1039/d2sc03771h…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And it is found that the introduction of uorine in the tetrahedron can enhance the birefringence or optimize the dispersion of refractive indices, TO 4−x F x (T = B, x = 1-4; T = P, x = 1-2; T = S, and x = 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] Planar p-conjugated anionic groups, such as BO 2 , BO 3 , B 3 O 6 , C 3 N 3 O 3 , CO 3 , NO 3 , etc., [35][36][37][38][39][40][41][42][43][44] Cite this: DOI: 10.1039/d2sc03771h…”
Section: Introductionmentioning
confidence: 99%
“…And it is found that the introduction of uorine in the tetrahedron can enhance the birefringence or optimize the dispersion of refractive indices, TO 4−x F x (T = B, x = 1-4; T = P, x = 1-2; T = S, and x = 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] Planar p-conjugated anionic groups, such as BO 2 , BO 3 , B 3 O 6 , C 3 N 3 O 3 , CO 3 , NO 3 , etc., [35][36][37][38][39][40][41][42][43][44] exhibit strong polarizability anisotropy, which are regarded as the preferred functional units to induce large birefringence. Borates with relatively wide transparency and large birefringence have been studied systematically in recent decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, we screened out an organic (C 3 H 2 O 4 ) 2À group because its configuration can be seen as two π-conjugated parts are connected via a non-π-conjugated part. [20] As expected, benefiting from the "π-conjugated confinement" effect, (C 3 H 2 O 4 ) 2À group shows a large LUMO-HOMO gap, which has the potential to be used in deep-UV region. More importantly, since it is a flexible unit, the hyperpolarizability and polarizability anisotropy can be modulated by rotation of the group, which is conductive to achieving a balance between strong SHG response and moderate birefringence.…”
Section: Introductionmentioning
confidence: 52%
“…In related systems, lots of birefringent materials have been reported, for example, α-BBO, Li 2 Na 2 B 2 O 5, Ca­(BO 2 ) 2, Cs 2 Pb­(NO 3 ) 2 Br 2, LiZn­( OH )­CO 3, Li 3 La 2 (BO 3 ) 3, In­(IO 3 ) 2 (NO 3 ), and ABCO 3 F-type compounds. For these π-conjugated planar groups, the generation of large birefringence requires their arrangement in coplanar or coaxial manner. Otherwise, it will get a small birefringence. Metal oxides containing stereochemically lone pair electrons (like Pb 2+ , Se 4+ , Te 4+ ) are also a type of potential birefringent material . The SCALP cations can cause large structural distortion and contribute greatly to the optical anisotropy, so they can enhance the birefringence of materials. In addition, the introduction of SCALP cations is considered more effective in improving the birefringence of compounds because it has a relatively lower requirement for the group arrangement.…”
Section: Introductionmentioning
confidence: 99%